2005
DOI: 10.1097/01.yct.0000159325.08303.45
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in Drug-Induced Psychiatric States and Neuroleptic Malignant Syndrome

Abstract: In the late-stage idiopathic Parkinson's disease (IDP), comorbid conditions such as depression and drug-induced psychosis may be observed. A patient with Parkinson disease, major depression, and paranoid psychosis who developed neuroleptic malignant syndrome (NMS) as the result of the sudden termination of high-dose (1200 mg/d) levodopa treatment is presented in this report. Because the patient did not respond to other treatment modalities, electroconvulsive therapy (ECT) was applied, and a rapid improvement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 26 publications
0
21
0
3
Order By: Relevance
“…Electroconvulsive therapy (ECT) has also been reported to be effective in reversal of signs of NMS toxicity in refractory or prolonged cases of muscle rigidity. Various case reports have suggested that ECT might be an effective and life-saving therapy in patients with severe drug resistant NMS, and therefore should be strongly considered in such a situation [20,21]. ECT was initially considered in our patient after no improvement in her clinical condition after 7 days, but her mental state and muscle rigidity was notably better the following day, and we did not proceed with this therapeutic option.…”
Section: Discussionmentioning
confidence: 98%
“…Electroconvulsive therapy (ECT) has also been reported to be effective in reversal of signs of NMS toxicity in refractory or prolonged cases of muscle rigidity. Various case reports have suggested that ECT might be an effective and life-saving therapy in patients with severe drug resistant NMS, and therefore should be strongly considered in such a situation [20,21]. ECT was initially considered in our patient after no improvement in her clinical condition after 7 days, but her mental state and muscle rigidity was notably better the following day, and we did not proceed with this therapeutic option.…”
Section: Discussionmentioning
confidence: 98%
“…Some case reports suggest that electroconvulsive therapy (ECT) may be an option to consider in patients with PD and comorbid depression [155][156][157][158][159][160][161] or psychosis. 162,163 Open-label studies have also suggested that repetitive transcranial magnetic stimulation (rTMS) may have utility in the treatment of depression in PD.…”
Section: Nonpharmacological Interventions For Emotional Disturbances mentioning
confidence: 99%
“…Mehrere Fallberichte sprechen für eine mögliche Wirksamkeit von EKT, um psychotische Symptome bei Patienten mit PDP zu reduzieren, die ansonsten resistent gegen antipsychotische Behandlungen waren [137][138][139][140]. Ueda et al berichteten über eine positive retrospektive Studie bei fünf resistenten Patienten mit PDP [141].…”
Section: Elektrokrampftherapie (Ekt)unclassified